2014
DOI: 10.1161/circulationaha.113.006987
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Leadless Cardiac Pacing

Abstract: http://clinicaltrials.gov. Unique identifier: NCT01700244.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(134 citation statements)
references
References 24 publications
1
124
0
6
Order By: Relevance
“…Electrodes and leads, however, remain the weakest link which has led to the development of leadless pacemakers. (25) His bundle recording and EP studies…”
Section: Pacemakersmentioning
confidence: 99%
“…Electrodes and leads, however, remain the weakest link which has led to the development of leadless pacemakers. (25) His bundle recording and EP studies…”
Section: Pacemakersmentioning
confidence: 99%
“…However, main components of current pacemakers are still the same of the first cardiac pacemaker type, such as a pulse generator and one or more transvenous leads. This design usually causes some shortterm and long-term complications (in approximately 10% of patients) [4,20]. The subcutaneous pocket is very prone to local infections and often causes skin erosion and hematoma inside the implantation region [20].…”
Section: Leadless Cardiac Pacemaker (Lcp) As a New Minimal Invasive Mmentioning
confidence: 99%
“…In addition, implantation procedures of this regular pacemaker also have several risks. In the short-term, it can cause mobility limitations, pneumothorax, cardiac tamponade and upper limb Deep Vein Thrombosis (DVT) [3,4,6,19]. A study showed that up to six out of ten patients with regular pacemakers developed mobility limitations in the shoulder region, where the pulse generators were implanted [6].…”
Section: Leadless Cardiac Pacemaker (Lcp) As a New Minimal Invasive Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, central lines (vascular catheters) should be avoided in patients with CIED devices, because they may be associated with higher risk of mortality from infection. 34 Leadless pacemaker technology provides an alternative that does not require pockets or leads 65,66,67 and therefore avoids many of the problems associated with intravascular lead use, including pocket infection. This represents an important therapeutic advance in suitable patients.…”
Section: Strategies To Prevent Cardiac Implantable Electronic Device mentioning
confidence: 99%